Percept and perceptual judgment in Peirce’s phenomenology - Luisi, Maria (Cognitio-Estudos: revista eletrônica de filosofia, 2011)
Between 1900 and 1908 Peirce wrote many papers about phenomenology and theory of perception. The most important are the series of seven lectures that Peirce delivered in Harvard on 1903 and a long manuscript that he composed few months later, called On Telepathy. In those writings our perceptual experience is described as composed by two elements. The first one is the pure reaction against the blow of the external object, which is almost forced upon us; it’s called percept. The second element belongs to the order of interpretation and it’s called perceptual judgment. It’s very important to find a connection between those two parts because in our experience we cannot recognize a sharp line of demarcation: the moment of reaction and passivity seems to shade progressively into the interpretation of the percept. A solution for this problem is presented in On Telepathy, where Peirce introduces a new term: percipuum. It represents our perceptual experience, considered for his essential relation with continuum. The link between continuity and perception shows itself through the link between time and perception. Percipuum can never be isolated, but it’s always spread out in a lapse of time and we know that in Peirce’s philosophy time is the most authentic continuous phenomenon. If time is a continuum and time constitutes the primary structure of every perceptual experience, then perceptual experience itself will have to be continuous. After 1903 the word percipuum disappears from Peirce’s writings but the importance of continuity grows more and more, because every process of our knowledge is authentically semiotic from the beginning.